Bulk nanocrystalline high-strength magnesium alloys prepared via rotary swaging. (November 2020) - Wan, Yingchun; Tang, Bei; Gao, Yonghao; Tang, Lingling; Sha, Gang; Zhang, Bo; Liang, Ningning; Liu, Chuming; Jiang, Shunong; Chen, Zhiyong; Guo, Xueyi; Zhao, Yonghao
Abstract: Being lightweight, energy-efficient and environmentally benign, magnesium alloys present great potential for various industrial applications. However, they possess relatively low mechanical properties and need to be strengthened. During the last decade, significant effort has been directed towards preparation of strong nanocrystalline (NC) Mg alloys, although because of the limited plasticity inherent to HCP metals, the grain size of Mg was rarely refined below 1000 nm and the yield strength seldom exceeded 500 MPa. Here, by means of a conventional industrial method of rotary swaging, we prepared bulk NC Mg–Gd–Y–Zr alloys with an average grain size of 80 nm and a dimension of ∅3 mm × 1000 mm. The further-aged NC Mg alloy exhibits the yield strength of 650 MPa and the ultimate tensile strength of 710 MPa, the highest such values published for bulk Mg alloys. Fracture surface observation suggested a ductile inter-granular fracture in the NC Mg alloys. The high strength are attributed to nano-grain, intra-granular Gd rich clustering, inter-granular solutes segregation, β′ precipitation, dislocation and solution strengthening contributions, among which the nano-grain strengthening is dominant. The nano-grain formation results from the large number of mechanical twins, deformation bands and stacking faults induced by the high strain rate of swaging. Our work advances the industrial-scale production of bulk NC Mg alloys by exploring a simple and low-cost fabrication technique. Graphical abstract: Image, graphical abstract